Jerome Robbins: His Life, His Teacher, His Dance Book review - Sansom, Bruce (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Robbins spared himself little sympathy in his personal notes, and Jowitt doesn't hesitate to reveal aman tortured by artistic and personal self-doubt. PALABRAS CLAVE: Jerome Robbins.
Dentro del apartado " Shelf Content".
Jerome Robbins: His Life, His Teacher, His Dance. Deborah Jowitt, Simon & Schuster. 2004.